Optimizing an eco-friendly high-density concrete for offshore applications: A study on fly ash partial replacement and graphene oxide nano reinforcement - Udeze O.J.; Mohammed B.S.; Adebanjo A.U.; Abdulkadir I. (Elsevier Ltd, 2025)
There is a need in enhancing high-density concrete (HDC) for safeguarding sub-sea pipelines and constructing concrete mattresses for pipeline stabilization. To tackle these issues, a novel approach using a combination of supplementary cementitious materials like fly ash (FA) and graphene oxide (GO) have been successfully used in the partial replacement of the cement in this study. This research aims to enhance density, water resistance, and compressive strength properties for offshore applications by using GO and FA. A central composite design (CCD) of the response surface methodology (RSM) was employed, generating thirteen mixes with varying dosages of GO in the range of 0.013%?0.053% by weight of the cement and FA in the range of 20%?50% by weight of the cement. The HDC mixes exhibited enhanced characteristics, including an increased density of 4282 kg/m?, a maximum compressive strength of 37.9 MPa, and reduced water absorption at 2.52%. Response predicted models were established and validated through ANOVA, and multi-objective optimization was performed at a desirability of 58%. This yielded optimal GO and FA dosages of 0.013% and 37.87% respectively, for HDC with improved performance. The R2 values for the models range from 70% to 96%, showing a good level of the model quality. The findings present promising opportunities for more sustainable, cost-effective, and environmentally friendly HDC solutions for offshore applications. ? 2023 The Authors